الابعاد الاقتصادية للحكومة الالكترونية - خولة رشیج حسن (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص یعد موضوع الحكومة الالكترونیة من المواضیع المهمة والحدیثة على الساحتین الدولیة والإقلیمیة، الادارة الالكترونیة هي E-Government فالحكومة الالكترونیة او بمعنى وترجمة دقیقة لمصطلح منظومة الكترونیة متكاملة تهدف الى تحویل العمل الاداري العادي من ادارة یدویة الى ادارة باستخدام الحاسوب وذلك بالاعتماد على نظم معلوماتیة قویة تساعد على اتخاذ الق ا رر الاداري بأسرع وقت واقل كلفة. ومن هذا المنطلق ولأهمیة الموضوع وحداثته جاءت هذه الد ا رسة لتسلیط الضوء على هذا الموضوع بالبحث في ماهیته ومتطلباته ومن ثم ابعاده الاقتصادیة. وتنطلق الد ا رسة من فرضیة مفادها (ان للحكومة الالكترونیة ابعاد اقتصادیة على البلدان المختلفة التي تطبقها وعلى الاخص فیما یتعلق بالتجارة الالكترونیة اذ ان هناك علاقة قویة بینهما والتي تتمثل في الاسالیب الالكترونیة وأبرزها تقنیة المعلومات والاتصالات). Abstract The subject of the e-government of important topics and modern international and regional arenas , the government electronic or sense and accurate translation of the term E-Government E-governance is the system integrated electronic aims to transform the administrative work normal administration handy to run using the computer , based on information systems strong help decision as soon as the administrative and less expensive . From this point to the importance of the subject and the novelty of this study was to shed light on the subject and what it looks in its requirements and then economic dimensions. The study started from the premise that ((e-government that a significant impact on the economic level and related topics such as trade through electronic methods used e)) . Accordingly, this study has addressed the subject of research and analysis through a review of the concept of egovernment , and these types of governments and objectives , and then highlight the requirements of e-government and economic deported